Association between MRI findings and patient‐reported outcomes in patients with rheumatoid arthritis in clinical remission and at relapse. (28th January 2020) - Glinatsi, Daniel; Brahe, Cecilie H.; Hetland, Merete L.; Ørnbjerg, Lykke; Krabbe, Simon; Baker, Joshua F.; Boesen, Mikael; Rastiemadabadi, Zoreh; Morsel‐Carlsen, Lone; Røgind, Henrik; Hansen, Annette; Nørregaard, Jesper; et al.
Abstract: Objective: To investigate whether magnetic resonance imaging (MRI) pathologies in the wrist/hand of rheumatoid arthritis (RA) patients are associated with patient‐reported outcomes (PROs) at clinical remission and relapse. Methods: Wrist/hand MRIs and wrists/hands/feet radiographs were obtained in 114 established RA patients in clinical remission, before tapering their biologic disease‐modifying antirheumatic drugs. MRIs were assessed according to the Outcome Measures in Rheumatology (OMERACT) RA MRI score (RAMRIS) for inflammation (synovitis/tenosynovitis/bone marrow edema) and damage (bone erosion/joint space narrowing) at baseline (ie remission) and in case of a relapse (n = 70). Radiographs were assessed according to the Sharp/van der Heijde (SvH) method at baseline. These scores were assessed for associations with health assessment questionnaires (HAQ), visual analog scales (VAS global/pain), EuroQol‐5 dimensions and Short‐Form 36 physical and mental component summary (SF‐36 PCS/MCS) using Spearman correlations, univariate/multivariable linear regression analyses and generalized estimating equations. Furthermore, MRI pathologies were assessed for association with specific hand‐related HAQ items using Jonckheere trend tests. Results: Magnetic resonance imaging‐assessed damage was associated with impaired HAQ and SF‐36 PCS at remission and relapse ( P < .01), independent of clinical and radiographic measures, and was also associated with most of the hand‐related HAQ items ( P < .03). In multivariate models including MRI, SvH scores were not associated with PROs. MRI‐assessed inflammation was not associated with PROs at remission or relapse. Conclusion: Magnetic resonance imaging‐assessed wrist/hand damage, but not inflammation, in patients with established RA is associated with patient‐reported physical impairment at remission and relapse. The amount of damage in the wrist/hand is associated with reduced hand function.